Fire Briquette Enterprise / Masro Masag...[et.al] - Masag, Masro; Waali, Nur Atikah; Abd Hamid, Mohd Khairi; Yusof, Mohamad Afiq Yusri; Abu Hassan, Mohd Taufiq Zulhelmy; Said Hamzah, Syed Muhamad Anasrullah (Faculty of Plantation and Agrotechnology, 2017)
Nowadays, our country faces with the biomass waste problems left in the agricultural activity either from industrial crop or secondary crop. In conjunction, to solved it, in our effort to minimize the amount of the waste and avoid it from pollute our eco-system, we need to find away to use the biomass as a source of energy or reusable products. Oil palm kernel shell biomass is one of the biomass that produce from the palm oil industry. It is a product that form after the process production of palm oil in the factory. Fire Briquette Enterprise is one of the company that has been established with the purpose to minimize the biomass leftover from the industry then form it into the reusable product as a charcoal and deodorizer. The priority of our company is to produce a product that is environmental friendly that produce less pollution than normal product in the market. Our product formulated with natural ingredients (palm kernel shell). This product can promote a healthy environment, less pollution around us. We had chosen Lot 43, Jalan Teratai, KM5 off Jalan Meru, 41050 Klang, Selangor as our business location because it is a strategic trade area and nearby to the residential area. It will facilitate and easier for consumers and other buyers to purchase our product. Our target market is from food industry (grill industry, traditional dishes),convenience store, outdoor camping shop, art industry (blacksmith, goldsmith, keris maker) and medicine industry (charcoal tablet). We innovate this product in order to fulfill demand from government in effort to reduce environment pollution. The aim of production of the product is to upgrade from the normal charcoal (wood, coconut shell) that already in the market by enhancing the quality and the features. Our company's target is to get profit of market about 10% for first year we enter the market and continue to increase to 10% for year after.In operating this business, our company, Fire Briquette Enterprise, will be managed by board of directors team which is organized by General Manager (GM), Admin Manager (AM),Marketing Manager (MM), Operation Manager (OM) and Financial Manager (FM) and Assistant Financial Manager (AAM) to ensure the business run smoothly and on a right track. The board has their own functions and talents which make them able to work effectively. A lawful agreement had been made between us, in front of the lawyer. The reason for this agreement is to make sure that all the business operation goes according to the schedule towards grasping our company goal.